The interdependent hemodynamic influence between abdominal aortic aneurysm and renal artery stenosis - Jiaqi Lim; Hung Dong Truong; Tae Yoon Song; Wilkin Jing Han Giam; Evelyn Linyi Koh; Justin Kok Soon Tan (Scientific Reports)
Abstract Cardiovascular diseases remain a leading cause of morbidity and mortality worldwide with abdominal aortic aneurysm (AAA) and renal artery stenosis (RAS) standing out as significant contributors to the vascular pathology spectrum. While these conditions have traditionally been approached as distinct entities, emerging evidence suggests a compelling interdependent relationship between AAA and RAS, challenging the conventional siloed understanding. The confluence of AAA and RAS represents a complex interplay within the cardiovascular system, one that is often overlooked in clinical practice and research. Here, we reveal a bidirectional consequential impact between these two diseases. The location of the AAA sac was investigated for its specific influence on the risk of RAS development. Although studies have shown a higher coincidence between the suprarenal AAA and RAS, our findings demonstrated that the presence of a suprarenal AAA correlated with the lowest risk of RAS development among the three investigated AAA locations. Notably, we also highlighted that the pre-existence of stenosis in the renal artery poses an elevated risk for the formation of suprarenal AAA, assessed by an increased wall shear stress gradient on the aortic wall. Our findings prompt a paradigm shift in the understanding and treatment of AAA and RAS in clinical practice.